2023
DOI: 10.1001/jamanetworkopen.2023.15235
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Stroke Recurrence, Cardiovascular Events, and Death Among Patients With Pregnancy-Associated vs Non–Pregnancy-Associated Stroke

Abstract: ImportanceWomen with pregnancy-associated stroke might have different risks of stroke recurrence, including during subsequent pregnancies, and other cardiovascular events due to pregnancy-specific stroke risk factors, such as gestational hypertension, preeclampsia, or gestational diabetes.ObjectiveTo estimate the rate of stroke recurrence, cardiovascular hospitalization, and death in women with pregnancy-associated stroke compared with women with non–pregnancy-associated stroke.Design, Setting, and Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 26 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…As 92.4% of controls and 92.3% of cases were under 60 years of age in 2016, most of the women were on pension due to disease or disability. Data on the long-term morbidity of patients with a maternal stroke are limited to subsequent cardiovascular morbidity described by Béjot et al 13 This French study found that a stroke recurred in 6.3% of women with a prior maternal stroke and that 13.6% were hospitalized for another cardiovascular event. 13 The risk of both stroke recurrence and other cardiovascular diseases was lower in comparison with that of matched women with a history of a stroke not associated with pregnancy or puerperium.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…As 92.4% of controls and 92.3% of cases were under 60 years of age in 2016, most of the women were on pension due to disease or disability. Data on the long-term morbidity of patients with a maternal stroke are limited to subsequent cardiovascular morbidity described by Béjot et al 13 This French study found that a stroke recurred in 6.3% of women with a prior maternal stroke and that 13.6% were hospitalized for another cardiovascular event. 13 The risk of both stroke recurrence and other cardiovascular diseases was lower in comparison with that of matched women with a history of a stroke not associated with pregnancy or puerperium.…”
Section: Discussionmentioning
confidence: 97%
“…Data on the long-term morbidity of patients with a maternal stroke are limited to subsequent cardiovascular morbidity described by Béjot et al 13 This French study found that a stroke recurred in 6.3% of women with a prior maternal stroke and that 13.6% were hospitalized for another cardiovascular event. 13 The risk of both stroke recurrence and other cardiovascular diseases was lower in comparison with that of matched women with a history of a stroke not associated with pregnancy or puerperium. 13 Regardless of a longer follow-up in our study, the stroke recurrence was similar to that reported in France.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations